(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: The disease caused by the new coronavirus (SARS-CoV-2), has affected the world population in several aspects. From the first information produced and disseminated, a plural image was built on this condition. Social networks, formal and informal, contributed to this construction. Objectives: To analyze the images of COVID-19 shown on the social network Instagram, as well as the symbols associated with the beginning of the pandemic. Methods: This is a descriptive study in which images related to COVID-19 were searched from Instagram. The search engine was carried out using hashtags and was carried out at the beginning of the pandemic. The images classified as “relevant” by the social network were selected and, then, the inclusion criteria were applied. The images were analyzed according to their meanings and symbols and based on the hermeneutic proposal of Hans-Georg Gadamer. Results: Four units of meaning were perceived, namely: Pharmacological coping measures; non-pharmacological coping measures; New ways of life; and Emotions and feelings raised by the pandemic. Non-pharmacological measures such as the use of Personal Protective Equipment (PPE) for prevention and control, in addition to the strategies of distance and social isolation were more representative. Conclusion: The image of COVID-19 on the social network Instagram was related to the non-pharmacological coping measures that changed the habits of the entire population and reflected in changes in their practices. However, we have doubts as to its application, considering the time of spread of the disease that extends to the present date.